Effects of moderate electric fields on cold-set gelation of whey proteins - From molecular interactions to functional properties - Rodrigues, Rui Miguel Martins (2020)
Whey protein gelation and final gel properties are dependent of the gel forming solution characteristics (e.g. protein concentration, pH, ionic strength), and physical variables involved in the method used for gel preparation. Ohmic heating (OH) is an emerging technology in food processing and its application in heat-induced gelation of whey proteins has demonstrated its capacity to influence the physicochemical properties of protein gels. In this work, we studied the OH process and its inherent moderate electric field (MEF) variables - i.e. electric field (EF) strength and frequency - in order to establish their influence in protein aggregation and gelation during WPI cold-set gels formation. The presence of the EF during OH, particularly at higher EF strengths conjugated with lower frequencies, contributed to the formation of smaller aggregates with lower content of reactive thiol groups and lower viscosity. The cold-set gels produced from the aggregates suspension presented distinctive properties, influenced by the EF variables. i.e. higher EF strength and lower frequency. EF treatments give rise to more fine-stranded gels with lower disulphide crosslinking but higher number of hydrophobic interactions and hydrogen bonds. The EF effects during the treatments resulted in weaker, more elastic gels with higher water retention and swelling capacity. These results open novel perspectives for the use of OH as a tool for fine-tuning protein gel networks aiming at enhanced functionality for various applications (e.g. use as texturizer or encapsulating agents).